Strategi Pembentukan Kesetaraan Gender dalam Upaya Harmonisasi Keluarga Islam - Naila Salsabila (Mutawasith: Jurnal Hukum Islam, 2022)
This paper seeks to explain the strategy for establishing gender equality in an effort to harmonize Islamic families. The problem that often arises in the majority of family life is the strong patriarchal culture that causes double workloads, violence, economic marginalization or marginalization, subordination and stereotypes in family life. Therefore, the purpose of this paper is to determine the role of husband and wife division of labor in building a household in order to realize the harmonization of Islamic families in the frame of gender equality. The method used in this paper is descriptive analytical to find a solution to the problem, provide an overview or formulate the problem in accordance with the existing circumstances/facts. The results of this study explain that a harmonious family can be built through the division of work roles whether it is domestic, public, social, or socio-cultural between husband and wife, son or daughter, between parents and children carried out fairly and equally for then becomes a gender partnership that makes harmonization in the family.